Exploring Feedback Loops to Enhance Community Wellbeing: Utilizing System Dynamics with Text Network Analysis - Young-Chool Choi (International Journal of Advanced Science and Technology, 2020)
This paper attempts to explore theoretically the reinforcing and balancing feedback loops that exist within the system of community wellbeing, and to put forward policy suggestions for strengthening the level of community wellbeing in a country on the basis of these feedback loops. Feedback loops – reinforcing or balancing feedback loops – play an important role in the entire policy system, such that policymakers can use them to identify the main sub-systems within a system and to manage and control the whole policy process as they wish. To this end, this paper employs the system dynamics approach, which has rarely been utilized in the field of community wellbeing study, and it also uses text network analysis to compensate for the weak points inherent in the system dynamics approach. The analysis results show that there are two reinforcing feedback loops and four balancing feedback loops within a community wellbeing policy system. From a policy point of view, it is hoped that, as a result of this research, policymakers involved in community wellbeing policies in a country at central or local level can recognize the existence of these six feedback loops in making and implementing the related policies and measures, and that they may sometimes be able to control them properly and manage them appropriately.